2010
DOI: 10.1038/nature08787
|View full text |Cite
|
Sign up to set email alerts
|

Orm family proteins mediate sphingolipid homeostasis

Abstract: Despite the essential roles of sphingolipids as both structural components of membranes and critical signalling molecules, we have a limited understanding of how cells sense and regulate their levels. Here we reveal the function in sphingolipid metabolism of the ORM/ORMDL genes, a conserved gene family that includes ORMDL3, which has recently been identified as a potential risk factor for childhood asthma. Starting from an unbiased functional genomic approach, we identify Orm proteins as negative regulators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
805
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 555 publications
(856 citation statements)
references
References 50 publications
41
805
2
1
Order By: Relevance
“…The use of myriocin is well established, and previous studies have demonstrated its ability to decrease the fraction of sphingolipids in various cell systems, including yeast (Breslow et al, 2010; Huang et al, 2012; Shimobayashi et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The use of myriocin is well established, and previous studies have demonstrated its ability to decrease the fraction of sphingolipids in various cell systems, including yeast (Breslow et al, 2010; Huang et al, 2012; Shimobayashi et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…A role of orm proteins in the regulation of sphingolipid synthesis has been well established in yeast for many years (24,28,(37)(38)(39) and has recently been demonstrated in human cells (40,41). ORMDL proteins act as negative regulators of sphingolipid synthesis by interacting with serine palmitoyl-coenzyme A transferase (SPT) (38).…”
Section: Ormdl3 and Sphingolipidsmentioning
confidence: 99%
“…ORMDL proteins act as negative regulators of sphingolipid synthesis by interacting with serine palmitoyl-coenzyme A transferase (SPT) (38). SPT catalyzes the condensation of serine and palmitoyl-coenzyme A, the rate-limiting step of the de novo sphingolipid synthesis (Figure 2).…”
Section: Ormdl3 and Sphingolipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ypk1 phosphorylates and inactivates Orm1 and Orm2 (Roelants et al, 2011), two major negative regulators of SPT (Breslow et al, 2010); hence, elevated Fpk1-mediated feedback inhibition of Ypk1 would be expected to impede all sphingolipid biosynthesis. However, total sphingolipid levels were not significantly altered in cells expressing Fpk1 11A compared with wild-type or fpk1 fpk2 cells (Fig.…”
Section: Screening For Novel Fpk1 Regulatorsmentioning
confidence: 99%